Brand Consciousness and Social Media Usage as Predictors of Body Dissatisfaction and Eating Disorder in Young Adult - Ayesha Asghar; Amna Liaqat; Dr. Amna Hassan, (Dialogue Social Science Review (DSSR), 2025)
The current study aimed to investigate the predictive role of brand consciousness and social media usage on body dissatisfaction and eating disorder symptoms among young adults. With the increasing influence of digital media and consumer culture, concerns over physical appearance and body image have intensified, particularly in younger populations. Correlational research design has been used, and the study sample consisted of 200 young adults aged 18-25 years and chosen using convenient sampling. Brand consciousness, social media use, body dissatisfaction, and eating disorder symptomology were measured using standardized instruments. The SPSS was used to conduct statistical tests (such as reliability tests, Pearson correlation, multiple regression). The results suggested a positive association between the brand consciousness and the presence of eating disorder.H1There is likely to be significant relationship between brand consciousness social media usage body dissatisfaction and eating disorder among young adult.H2. Nonetheless, the findings showed insignificant or negative correlations between brand consciousness and body dissatisfaction. The multi-regression models proved that brand consciousness and use of social media have a joint-predictive role in body dissatisfaction and eating disorder. H3There is no significant between gender and brand consciousness and social media usage body dissatisfaction and eating disorder. (These results support the need to consider both consumerism and social media in its damaging effects on psychological well-being, specifically as it relates to body image and disordered eating behavior. Discussions of the implications to public health interventions and media literacy education are provided. Keywords: Brand Consciousness, Social Media Usage, Body Dissatisfaction, Eating Disorder, young Adults